HBV-related hepatocellular carcinoma: The role of integration, viral proteins and miRNA - Lim, L.; Tran, B.; Vincan, Elizabeth; Locarnini, S.; Warner, N. (2012)
The development of hepatocellular carcinoma during chronic hepatitis B infection is a multifactorial process thought to be a consequence of several direct and indirect mechanisms. In this review we discuss how viral proteins and cycles of ongoing liver damage and regeneration, coupled with HBV DNA integration and aberrant miRNA expression may enhance the risk for the development of hepatocellular carcinoma. © 2012 Future Medicine Ltd.